Advancing Ehealth Education for the Clinical Health Professions - Gray, K.; Dattakumar, A.; Maeder, A.; Butler-Henderson, Kerryn; Chenery, H. (Office for Learning and Teaching, Department of Education, 2014)
This is the final report of a project that aimed to encourage and support program coordinators and directors of Australian undergraduate and postgraduate coursework programs in all allied health, nursing and medical professions to address the need for Ehealth education for entry-level clinical health professionals.